Anti‐Solvent Derived Non‐Stacked Reduced Graphene Oxide for High Performance Supercapacitors. (21st June 2013) - Yoon, Yeoheung; Lee, Keunsik; Baik, Chul; Yoo, Heejoun; Min, Misook; Park, Younghun; Lee, Sae Mi; Lee, Hyoyoung
<x xml:space="preserve">Abstract</x> An anti‐solvent for graphene oxide (GO), hexane, is introduced to increase the surface area and the pore volume of the non‐stacked GO/reduced GO 3D structure and allows the formation of a highly crumpled non‐stacked GO powder, which clearly shows ideal supercapacitor behavior. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>